2009
DOI: 10.1016/j.ahj.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of impedance cardiography with invasive hemodynamic measurements in patients with advanced heart failure: The BioImpedance CardioGraphy (BIG) substudy of the Evaluation Study of Congestive Heart Failure and Pulmonary Artery Catheterization Effectiveness (ESCAPE) Trial

Abstract: Background-Impedance cardiography (ICG) is a noninvasive modality that utilizes changes in impedance across the thorax to assess hemodynamic parameters, including cardiac output (CO). The utility of ICG in patients hospitalized with heart failure (HF) is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 15 publications
2
46
0
3
Order By: Relevance
“…22 At the largest randomised trial on heart failure patients -the BIG study as a part of ESCAPE study-only a modest correlation was observed between two techniques. 23 Results of our sample population affirm the strong relationship between invasive and ICG measurements of cardiac output.…”
Section: -21supporting
confidence: 50%
“…22 At the largest randomised trial on heart failure patients -the BIG study as a part of ESCAPE study-only a modest correlation was observed between two techniques. 23 Results of our sample population affirm the strong relationship between invasive and ICG measurements of cardiac output.…”
Section: -21supporting
confidence: 50%
“…Thus, hemodynamic parameters and the volemic status can be estimated. Although TIC has been evaluated in some clinical situations [6][7][8][9] , some questions remain on its accuracy and usefulness 10 . Cardiac magnetic resonance imaging (CMRI) is considered the gold-standard for the calculation of cardiac volumes 11,12 , and no previous study comparing the two methods has ever been conducted.…”
mentioning
confidence: 99%
“…The working hypothesis behind the use of transthoracic bioimpedance, despite some controversial evidence 36 is that when comparing surface and invasive measurements simultaneously, a significant correlation is found between thoracic conductance and pulmonary wedge pressure. 22,24 In fact, thoracic conductance has proven useful in detecting high-risk heart failure patients 25 and in identifying severe diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%